EFEKTIVITAS MEDIA FLASHCARD UNTUK MENINGKATKAN HASIL BELAJAR MATERI ASMAUL HUSNA PESERTA DIDIK KELAS VII DI SMP NEGERI 5 PALOPO - Muhammad, Fadil; Kahfi, Ashabul; Asdar; Hasriadi; Erwatul (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2025)
This study aims to determine the effectiveness of flashcard media on students’ learning outcomes and learning activities in the teaching of Asmaul Husna at SMP Negeri 5 Palopo. The study used a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The sample consisted of two classes: class VII A as the experimental group and class VII B as the control group, each with 27 students. The instruments used were learning outcome tests (pretest and posttest) and student activity observation sheets. The results showed that the use of flashcard media significantly improved students’ learning outcomes. The average posttest score of the experimental group was 83.70, higher than the control group's score of 71.29. Furthermore, the learning activity of students in the experimental class was categorized as very good with an average percentage of 96.19%. Thus, flashcard media is effective for Islamic religious education, particularly in teaching Asmaul Husna.